2004
DOI: 10.1128/iai.72.3.1733-1745.2004
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Late-Stage Disease in Mice Infected bythe Mycobacterium tuberculosis Mutant Lacking theSigF Alternate Sigma Factor and Identification ofSigF-Dependent Genes by MicroarrayAnalysis

Abstract: The Mycobacterium tuberculosis alternate sigma factor, SigF, is expressed during stationary growth phase and under stress conditions in vitro. To better understand the function of SigF we studied the phenotype of the M. tuberculosis ⌬sigF mutant in vivo during mouse infection, tested the mutant as a vaccine in rabbits, and evaluated the mutant's microarray expression profile in comparison with the wild type. In mice the growth rates of the ⌬sigF mutant and wild-type strains were nearly identical during the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 60 publications
6
110
3
1
Order By: Relevance
“…It was one of the genes with the largest reduction in transcription during early stationaryphase growth of a M. tuberculosis mutant harbouring a deletion of the gene encoding s F (Geiman et al, 2004), and it has been shown to interact physically with this sigma factor in a two-hybrid system (Parida et al, 2005). Its coinduction with s E opens the interesting hypothesis that this protein could be involved in the regulation of the activity of this sigma factor.…”
Section: Resultsmentioning
confidence: 99%
“…It was one of the genes with the largest reduction in transcription during early stationaryphase growth of a M. tuberculosis mutant harbouring a deletion of the gene encoding s F (Geiman et al, 2004), and it has been shown to interact physically with this sigma factor in a two-hybrid system (Parida et al, 2005). Its coinduction with s E opens the interesting hypothesis that this protein could be involved in the regulation of the activity of this sigma factor.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription of Cel6 was predictable, as this gene has been cloned and the encoded protein is expressed in Escherichia coli in an active form (Varrot et al, 2005). Moreover, the Cel6 gene has been shown to be downregulated in an M. tuberculosis mutant lacking SigF (Geiman et al, 2004), indicating that the regulation of this gene is SigF-dependent. The Cel12 gene lacks a peptide signal and exhibits a potentially fragmented structure which could suggest gene decay.…”
Section: Discussionmentioning
confidence: 99%
“…While none of the mutants was impaired in growth in broth culture or human macrophages in vitro, they showed reduced virulence in mouse and guinea pig infection models (Chen et al, 2000;Geiman et al, 2004;Karls et al, 2006). Furthermore, it was shown that SigF was required for survival of M. tuberculosis in the lung, but not in the spleen of guinea pigs (Karls et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…No induction compared to unexposed control cells was observed under these conditions (data not shown), confirming that the observed induction of rsbW-lacZ was indeed due to exposure to D-cycloserine. In M. tuberculosis, SigF appears to have a role in the regulation of genes involved in cell envelope biosynthesis (Geiman et al, 2004;Williams et al, 2007). It may therefore be that cell wall stress, e.g.…”
mentioning
confidence: 99%